The Distribution of Service Time at Bangi, Kajang, Sungai Besi and Universiti Pertanian Malaysia Closed System Toll Plazas - Radin Sohadi, Radin Umar; Midi, Habsah; Ja'afar, Mohd Salleh (1991)
The driver's service time at Bangi, Kajang, Sungai Besi and Universiti Pertanian Malaysia (UPM) closed system toll plazas was studied. A preliminary analysis was made to see if different days as well as different booths are homogenous with respect to service time. The goodness of fit test was used to determine the distribution of the service time. The results of the study show that there is no significant difference between days and booths with respect to service time. The distribution of service time for the four plazas was found to be a log-normal. The estimated,values of the mean service time at Bangi, Kajang, Sungai Besi and Universiti Pertanian Malaysia toll plazas are 13.87, 10.07, 13.87 and 7.32 seconds, respectively. This information is an important input in evaluating and improving the transportation system designed. Appropriate measures can be taken to ensure a more efficient toll plaza system in this country.